Analyse de l’expérience d’enseignants-chercheurs stagiaires dans un dispositif de vidéo-formation à la pédagogie universitaire - Cyrille Gaudin (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The requirement for newly qualified associate professors to follow pedagogic training during their probation year is recent in France. Among the training tools implemented in the universities, those providing access to videos have grown progressively. Nevertheless, few studies have analyzed higher education teachers video training. As part of a research program about professional training, this study examines an innovative measure a university pedagogical video training innovative device for newly qualified associate professors. The innovating character of the tool resides in its approach in exploiting videos showing the students’ point of view, via videotape self-confrontation and videotape observations of others. The research was led from self-confrontation interviews with seven voluntary associate professors in their probation year out of a variety of university departments. The study aims at fixing the process effects. The results show that the different types of videos (class teaching situations footage, associate professors’ comments footage, students’ comments footage, and the associate professor’s reactions confronted with the students’ comments footage) and the content (“successful” and “perfectible” teaching practices) establish a “capacity-building” resource for probationary associate professors in terms of projection-immersion, satisfaction, and apprenticeship/professional development. The results also confirm the importance of screenwriting and the fact of respecting the principle of creating video training, such as accompaniment, individualization and progressivity. Finally, the risks linked with the conception and implementation of this type of tool will be discussed.